Advances in dolomite land risk assessment for safe development within the current legislative framework : the case of Khutsong North in Merafong City, Gauteng Province, South Africa - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2023)
Dissertation (MSc (Engineering Geology))--University of Pretoria 2023.